Cross-Media Communications - Davidson, Drew (Play Story Press, 2026)
This text is an introduction to the future of mass media and mass communications – cross-media communications. Cross-media is explained through the presentation and analysis of contemporary examples and project-based tutorials in cross-media development. The text introduces fundamental terms and concepts, and provides a solid overview of cross-media communications, one that builds from a general introduction to a specific examination of media and genres to a discussion of the concepts involved in designing and developing cross-media communications. CMC Media Files show how cross-media can be applied, with art, music and illustrations that complement the text. Chapters have overviews and problem-based/project-based activities to encourage active engagement with the readings. Throughout the text there are specific examples, case studies, foundations, and interviews with experts in the field to better illustrate the nature of cross-media. Cross-media Communications are integrated, interactive experiences that occur across multiple media, with multiple authors and have multiple styles. The audience becomes an active part in a cross-media experience. The overarching goal is to provide an overview of cross-media design and development. It is meant to be interdisciplinary and introductory in concept and implementation.